Genome Sequence of Salarchaeum sp. Strain JOR-1, an Extremely Halophilic Archaeon from the Dead Sea - Anton, Brian P. (Microbiol Resour Announc, 2020)
An extremely halophilic archaeon, Salarchaeum sp. strain JOR-1, was isolated from the east coast of the Dead Sea, Kingdom of Jordan, and sequenced using single-molecule real-time (SMRT) sequencing. The GC-rich 2.5-Mbp genome was composed of a circular chromosome and a megaplasmid. The genome contained 2,633 genes and was incorporated into HaloWeb (https://halo.umbc.edu/).